A ROLAND BARTHES SEMIOTIC ANALYSIS OF THE CRANBERRIES “ZOMBIE” LYRICS - Anisyah Putri Febriyani; Dewi Sri Kuning (Elite Laboratory Jurusan Sastra Inggris Universitas Bangka Belitung, 2026)
This study aims to analyze the semiotic meanings embedded in the song “Zombie” by The Cranberries using the semiotic framework proposed by Roland Barthes. The study employs a qualitative semiotic approach with a descriptive-interpretative design to examine how meaning is constructed through three levels of signification: denotation, connotation, and myth. The data consist of selected lyric units obtained from the official album No Need to Argue (1994) and verified lyric sources. Data selection was conducted using purposive sampling based on specific criteria, including lexical repetition, symbolic expressions, references to violence and conflict, and linguistic indicators of agency. The analysis was carried out through a systematic procedure involving segmentation, coding (D–C–M), and multi-level interpretation. At the denotative level, the findings indicate that the lyrics explicitly represent violence, suffering, and the impact of armed conflict. At the connotative level, the song conveys deeper emotional and cultural meanings such as trauma, grief, anger, and the loss of humanity. At the level of myth, the analysis reveals how the lyrics construct and simultaneously challenge ideological narratives that normalize violence as an inevitable condition.The findings also demonstrate that linguistic features such as repetition, pronoun usage, and lexical choices function as key semiotic mechanisms in meaning construction. Methodologically, this study contributes by operationalizing Barthes’ semiotic model through a structured and replicable analytical framework. The study highlights that song lyrics function not only as artistic expressions but also as cultural texts that construct and critique ideological meanings.